math solve this question
Attachments:
![](https://hi-static.z-dn.net/files/de1/516e0868d7f0a10ef7012e5384df6f19.jpg)
Answers
Answered by
1
LHS=
![{a}^{3} + {b}^{3} {a}^{3} + {b}^{3}](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B3%7D++%2B++%7Bb%7D%5E%7B3%7D+)
RHS=
![(a + b) ({a}^{2} - ab + {b}^{2} ) \\ (a + b) ({a}^{2} - ab + {b}^{2} ) \\](https://tex.z-dn.net/?f=%28a+%2B+b%29+%28%7Ba%7D%5E%7B2%7D++-++ab+++%2B+%7Bb%7D%5E%7B2%7D+%29+%5C%5C++)
Finding product of RHS,
![= a( {a}^{2} -ab + b {}^{2} ) + b( {a}^{2} - ab + {b}^{2} ) \\ = a {}^{3} - {a}^{2} b + ab {}^{2} + {a}^{2} b - ab {}^{2} + b {}^{3} \\ = a {}^{3} + b {}^{3} = a( {a}^{2} -ab + b {}^{2} ) + b( {a}^{2} - ab + {b}^{2} ) \\ = a {}^{3} - {a}^{2} b + ab {}^{2} + {a}^{2} b - ab {}^{2} + b {}^{3} \\ = a {}^{3} + b {}^{3}](https://tex.z-dn.net/?f=+%3D+a%28+%7Ba%7D%5E%7B2%7D+-ab++%2B++b+%7B%7D%5E%7B2%7D+%29+%2B+b%28+%7Ba%7D%5E%7B2%7D+++-+ab+%2B++%7Bb%7D%5E%7B2%7D+%29+%5C%5C++%3D+a+%7B%7D%5E%7B3%7D++-++%7Ba%7D%5E%7B2%7D+b+%2B+ab+%7B%7D%5E%7B2%7D++%2B++%7Ba%7D%5E%7B2%7D+b+-+ab+%7B%7D%5E%7B2%7D++%2B+b+%7B%7D%5E%7B3%7D++%5C%5C++%3D+a+%7B%7D%5E%7B3%7D++%2B+b+%7B%7D%5E%7B3%7D+)
LHS=RHS
-----verified------
NOW FACTORISE-----:
![x {}^{3} y {}^{3} + \frac{1}{512} \\ x {}^{3} y {}^{3} + \frac{1}{512} \\](https://tex.z-dn.net/?f=x+%7B%7D%5E%7B3%7D+y+%7B%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B512%7D++%5C%5C+)
We can factorise this using above identity,
So,
![(xy) {}^{3} + ( \frac{1}{5} ) {}^{3} (xy) {}^{3} + ( \frac{1}{5} ) {}^{3}](https://tex.z-dn.net/?f=%28xy%29+%7B%7D%5E%7B3%7D++%2B+%28+%5Cfrac%7B1%7D%7B5%7D+%29+%7B%7D%5E%7B3%7D+)
Now, this is in the form of above identity
![a {}^{3} + b {}^{3} = (a + b )\: ({a}^{2} - ab + b {}^{2} ) a {}^{3} + b {}^{3} = (a + b )\: ({a}^{2} - ab + b {}^{2} )](https://tex.z-dn.net/?f=a+%7B%7D%5E%7B3%7D++%2B+b+%7B%7D%5E%7B3%7D++%3D+%28a+%2B+b+%29%5C%3A++%28%7Ba%7D%5E%7B2%7D++-+ab+%2B+b+%7B%7D%5E%7B2%7D+%29)
So,
![(xy + \frac{1}{8} )( \: (xy) {}^{2} - xy \times \frac{1}{8} + ( \frac{1}{8} ) {}^{2} \: ) \\ = (xy + \frac{1}{8} )(x {}^{2} y {}^{2} - \frac{xy}{8} + \frac{1}{64} ) (xy + \frac{1}{8} )( \: (xy) {}^{2} - xy \times \frac{1}{8} + ( \frac{1}{8} ) {}^{2} \: ) \\ = (xy + \frac{1}{8} )(x {}^{2} y {}^{2} - \frac{xy}{8} + \frac{1}{64} )](https://tex.z-dn.net/?f=%28xy+%2B++%5Cfrac%7B1%7D%7B8%7D+%29%28+%5C%3A+%28xy%29+%7B%7D%5E%7B2%7D+-+xy+%5Ctimes++%5Cfrac%7B1%7D%7B8%7D+++%2B+%28+%5Cfrac%7B1%7D%7B8%7D+%29++%7B%7D%5E%7B2%7D+%5C%3A+%29+%5C%5C++%3D+%28xy+%2B++%5Cfrac%7B1%7D%7B8%7D+%29%28x+%7B%7D%5E%7B2%7D+y+%7B%7D%5E%7B2%7D++-++%5Cfrac%7Bxy%7D%7B8%7D++%2B++%5Cfrac%7B1%7D%7B64%7D+%29)
Hope this will help you.
RHS=
Finding product of RHS,
LHS=RHS
-----verified------
NOW FACTORISE-----:
We can factorise this using above identity,
So,
Now, this is in the form of above identity
So,
Hope this will help you.
sukhdev9911p43j2h:
Himanshu i am upload 1 new question
Similar questions